ANTIMICROBIAL ACTIVITY OF METHANOL EXTRACT FROM MAHOGANY SEEDS Sri Mursiti, Supartono (SWIETENIA MACROPHYLLA, KING) (Universitas Negeri Semarang, 2016)
Mahogany seeds is one of the natural ingredients that can be used as an antimicrobial. This study aims to determine the antimicrobial activity of methanol extract mahogany seeds and determine the components of active compounds that have antimicrobial activity against Escherichia coli (E.coli) and Bacillus cereus (B.cereus). Extraction was done by maceration method with methanol and testing of antimicrobial activity using the absorption method. The results showed that the antimicrobial activity of methanol extract mahogany seeds shows inhibitory activity and provide clear zone against bacteria E.coli with value Inhibitory Regional Diameter 16,75 mm respectively, but did not give a clear zone of the bacterium B.cereus. Based on the results of the study it can be concluded that the methanol extract of seeds mahogany has antimicrobial activity against E.coli.